Strategi Pemasaran Beras Analog Di Desa Sumbersih Kecamatan Panggungrejo Kabupaten Blitar - Damayanti, Amelia; Widiatmanta, Jeka; Prayudhi, Luhur Aditya; Sativa, Rima Dewi Oryza (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
The research entitled Marketing Strategy of Analog Rice in Sumbersih Village, Panggungrejo District, Blitar Regency was conducted in Sumbersih Village, precisely located in Pehpulo Hamlet RT 01 RW 03 Sumbersih Village, Panggungrejo District, Blitar Regency, East Java. This study aims to (1) identify the marketing mix of analog rice products in Sumbersih Village, Panggungrejo Subdistrict, Blitar Regency, (2) analyze internal and external factors that affect the marketing of analog rice products in Sumbersih Village, Panggungrejo Subdistrict, Blitar Regency, (3) identify alternative marketing strategies for analog rice products in Sumbersih Village, Panggungrejo Subdistrict, Blitar Regency. The data analysis method in this study is to use the marketing mix, and the SWOT analysis method. The type of data used is qualitative data using primary data sources conducted by observation, interviews, and documentation and secondary data sources conducted by literature studies, research journals, and the internet. Based on the results of the study, the SWOT analysis at Kinasih MSMEs is in quadrant I with an SO strategy that supports aggressive growth.